Qualitative research and dental public health - Roslind Preethi George; Estie Kruger; Marc Tennant (Wolters Kluwer Medknow Publications, 2012)
The use of Qualitative Research (QR) methods are now getting common in various aspects of health and healthcare research and they can be used to interpret, explore, or obtain a deeper understanding of certain aspects of human beliefs, attitudes, or behavior through personal experiences and perspectives. The potential scope of QR in the field of dental public health is immense, but unfortunately, it has remained underutilized. However, there are a number of studies which have used this type of research to probe into some unanswered questions in the field of public health dentistry ranging from workforce issues to attitudes of patients. In recent health research, evidence gathered through QR methods provide understanding to the social, cultural, and economic factors affecting the health status and healthcare of an individual and the population as a whole. This study will provide an overview of what QR is and discuss its contributions to dental public health research.